Higher Lymph Node Metastasis Rate and Poorer Prognosis of Intestinal-Type Gastric Cancer Compared to Diffuse-Type Gastric Cancer in Early-Onset Early-Stage Gastric Cancer: A Retrospective Study - Tang, Chao-Tao; Chen, Si-Hai (Frontiers in Medicine, 2021)
Background: The incidence of early-onset gastric cancer (GC) is increasing, but there is a knowledge gap on early-onset early-stage GC (EEGC). Therefore, we comprehensively analysed the clinical features based on Lauren type. Methods: Logistic and Cox analyses were used to investigate risk factors for lymph node metastasis (LNM) and prognosis, respectively. Propensity score matching (PSM) was used to adjust confounding factors. Protein mass spectrometry analysis was used to explore the molecular mechanism of LNM. Result: Our study included 581 EEGC patients from the SEER database and 226 EEGC patients from our own centre We identified intestinal type, T1b stage and tumour size (>3 cm) as risk factors for LNM using SEER and our own data. We also found that the prognosis of intestinal-type EEGC patients was poorer than diffuse-type EEGC patients, and T1b stage and positive LNM were hazard factors for survival. After analysing the expression of proteins between positive and negative LNM in the intestinal or diffuse type, we found no similar proteins between these groups. The differentially expressed genes (DEGs) in the intestinal type functioned as epithelial cell signalling in Helicobacter pylori The DEGs in the diffuse type functioned in the TCA cycle and oxidative phosphorylation. Conclusion: For EEGC, our study was the first report to demonstrate that the intestinal type was a risk factor for LNM and survival compared to the diffuse type, and the oncogenic expression promoting the occurrence of LNM was different. These findings suggest that clinicians should pay more attention to intestinal-type EEGC than diffuse-type EEGC.